Digital Dissertations at Aalborg University Library - Arkin, Elizabeth (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
At present, digitization of Ph.D. theses occurs on a very limited basis in Denmark. Until recently the emphasis has been exclusively on creating and maintaining bibliographic databases containing references to published research literature, descriptions of research projects, and research profiles of institutes, laboratories or departments. The principal vehicle for this information in Denmark is the Danish National Research Database, , established by the Ministry of Research and Information Technology. The database, which is part of Denmark’s Electronic Research Library, presently contains about 150,000 research references. Recently Danish universities, mainly university libraries, have been taking steps toward adopting the role of electronic full text publisher.